Effect of aging state on corrosion fatigue properties of 7075 aluminum alloy. (August 2022) - Gong, B.S.; Zhang, Z.J.; Hou, J.P.; Duan, Q.Q.; Wang, X.G.; Zhang, Z.F.
Highlights: The effect of the aging state on the corrosion fatigue properties of Al alloy is related to the stress level. Under high-stress range where fatigue damage dominates, the over aged state shows better corrosion fatigue performance. Under low-stress range, the over aged state has lower corrosion fatigue lives for its facilitation on the pitting-induced cracking. Abstract: The corrosion fatigue performance of Al alloy components is crucial for their engineering applications. This study focuses on the corrosion fatigue properties of 7075 Al alloys in three different aging states, i.e. over-aging (OA), peak-aging (PA) and under-aging (UA) states. The results show that the fatigue damage mechanism of the Al alloy is greatly affected by the stress level. In the high-stress region where the cyclic number is short, the fatigue damage is mainly caused by dislocations accumulation and stress concentration on the grain boundary. Compared with the UA state, the wave slip dislocations at the OA state are easy to accumulate and annihilate at the second phase boundaries, which reduces the fatigue damage degree at the grain boundaries. However, in the low-stress range where the cyclic number is large, the corrosion fatigue life of the Al alloy is mainly controlled by pitting-induced crack initiation. For the OA state, the spacing and size of the precipitated phase are large, so it is easy to trigger corrosive pitting, which reduces the corrosion fatigue performance of the alloy.